Rainfall interception mapping in the Alto Juruá hydrographic basin, Acre (Research, Society and Development, 2022)
Rainwater interception losses are often neglected due to measurement difficulties and great spatial and temporal variability. Losses can be significant and therefore have a severe impact on the water balance of a watershed. The present work had as objective to obtain the pluvial interception in the hydrographic basin of the Alto Juruá (BHAJ), through the Gash model, based on remote sensing data. The platform for data processing was the Google Earth Engine, which allowed the assessment and comparison of rainfall variables, normalized difference vegetation index and leaf area index (LAI), on a monthly and annual scale, in the period of 2003 to 2016. Thus, it was possible to observe that the interception has a strong relationship with LAI and vegetation cover, recording an annual average of 11.2% of rain intercept by the forest within the BHAJ, with its highest percentages in the rainiest periods.